2021
DOI: 10.1016/j.jtocrr.2021.100237
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Targeted Inhibitors in Metastatic Lung Squamous Cell Carcinoma With EGFR or ALK Alterations

Abstract: Introduction The efficacy of targeted therapies in oncogene-driven lung adenocarcinomas (LUADs) has been well established; however, the benefit for EGFR -mutant or ALK -rearranged lung squamous cell carcinomas (LUSCs) is less known, partially owing to the rarity of the incidence. Methods We reviewed the database of the MD Anderson Cancer Center and identified metastatic LUSC with classic EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…EGFR or ALK gene alterations occur in patients with LUSC, especially non-smoking females, in which TKI treatments present clinical benefits in disease control with a considerably shorter drug-resistant duration in LUSC patients than in lung adenocarcinoma (LUAD) patients ( 9 ). A previous study ( 10 ) reported that the first-line pembrolizumab treatment was superior to conventional chemotherapy for lung cancer patients with high PD-L1 expression, and the subgroup analysis showed that pembrolizumab was more effective in treating LUSC than non-LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR or ALK gene alterations occur in patients with LUSC, especially non-smoking females, in which TKI treatments present clinical benefits in disease control with a considerably shorter drug-resistant duration in LUSC patients than in lung adenocarcinoma (LUAD) patients ( 9 ). A previous study ( 10 ) reported that the first-line pembrolizumab treatment was superior to conventional chemotherapy for lung cancer patients with high PD-L1 expression, and the subgroup analysis showed that pembrolizumab was more effective in treating LUSC than non-LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…33 ALK mutations are considered even rarer and have only been described in case studies. 34 Nevertheless, a recent retrospective analysis indicated that TKIs can render clinical benefit in SCC patients with targetable mutations. 34 In 8 patients with EGFR mutations, TKIs (osimertinib or erlotinib) conferred a disease control rate (DCR) of 88%.…”
Section: Tyrosine Kinase Inhibitors (Tkis) Directed Against Targetabl...mentioning
confidence: 99%
“…34 Nevertheless, a recent retrospective analysis indicated that TKIs can render clinical benefit in SCC patients with targetable mutations. 34 In 8 patients with EGFR mutations, TKIs (osimertinib or erlotinib) conferred a disease control rate (DCR) of 88%. In 4 patients with ALK mutations, TKIs were associated with a DCR of 67%.…”
Section: Tyrosine Kinase Inhibitors (Tkis) Directed Against Targetabl...mentioning
confidence: 99%
“…On the other hand, many driver alterations in NSCLC are considered ‘druggable’, and the development of agents targeting them has revolutionized the management of NSCLC treatment [ 30 , 48 , 83 ]. In particular, in genetically selected LUAD patients, molecularly targeted therapies provide significant superiority over standard platinum-based chemotherapy, and there are attempts to obtain similar results in LUSC [ 30 , 84 ]. In Table 2 we summarized the common driver alterations associated with LUAD and LUSC, indicating their frequency in TCGA (The Cancer Genome Atlas) database, as well as matching them with a potential clinical trial.…”
Section: Clinical Implication Of Driver Alterationsmentioning
confidence: 99%